Show me you care: female mate choice based on egg attendance rather than male or territorial traits. (31st May 2020) - Valencia-Aguilar, Anyelet; Zamudio, Kelly R; Haddad, Célio F B; Bogdanowicz, Steve M; Prado, Cynthia P A
Abstract: Female mate choice is often based on male traits, including signals or behaviors, and/or the quality of a male's territory. In species with obligate paternal care, where care directly affects offspring survival, females may also base their mate choices on the quality of a sire's care. Here, we quantified male reproductive success in a natural population of the glass frog Hyalinobatrachium cappellei, a species with male parental care, to determine the influence of territory quality, male traits, and paternal care behaviors on female mate choice. We found that attending males have a higher chance of gaining new clutches than nonattending males. Our results indicate that females do not select males based only on body condition, calling persistence, or territory traits. Instead, our findings support the hypothesis that females choose males based on care status. Indeed, males already attending a clutch were 70% more likely to obtain another clutch, and the time to acquire an additional clutch was significantly shorter. We also found that males adjust their parental care effort in response to genetic relatedness by caring only for their own offspring; however, remaining close to unrelated clutches serves as a strategy to attract females and increase chances of successful mating. Thus, males that establish territories that already contain clutches benefit from the signal eggs provide to females. Abstract : Females of a Neotropical glass frog prefer to mate with males that are already attending one or more clutches of eggs. In this species, parental care is critical for offspring survival; therefore, by choosing males already attending, females maximize their reproductive success. Males, in turn, remain close to unrelated clutches and use those as "fake signals" to increase their chances of attracting females.